1 Development of an adult low vision services quality framework - Gow, Louise; Singla, Preeti (BMJ open ophthalmology, 2025)
BackgroundUK low vision services are historically fragmented. Lack of standardised commissioning or clinical framework means many people with sight loss cannot access fit for purpose services. The Adult Low Vision Service Quality Framework was developed with extensive cross-sector collaboration to help improve commissioning and support the planning and evaluation of new/existing low vision services.MethodsLiterature searches on low vision standards, governance and service guidance were conducted. Following a survey of UK low vision practitioners we created a group of representatives from the hospital eye service, primary care optometry, orthoptics, universities, vision rehabilitation specialists, people with lived experience and third sector organisations to collaboratively determine the components of a high-quality low vision service and potential barriers to providing care. A draft framework was piloted within low vision sites before creating a final version. Good Practice Guidelines were produced to support and explain each of the criteria.ResultsThe result of this extensive 4-year collaboration is the publication of The Adult Low Vision Services Quality Framework, endorsed by 12 sector organisations plus supporting Good Practice Guidance.ConclusionIf the framework is adopted as a quality standard by all UK low vision services patients will be able to access timely, high-quality support wherever they live, and commissioners will be upskilled to make good decisions in terms of funding new services. The RNIB Adult Low Vision Services Quality Framework forms a key part of the commitment of the NHS to provide an eye care support pathway alongside the clinical care pathways.